Patient‐level predictors of achieving early glycaemic control in Type 2 diabetes mellitus: a population‐based study. Issue 11 (31st July 2016) - Svensson, E.; Baggesen, L. M.; Thomsen, R. W.; Lyngaa, T.; Pedersen, L.; Nørrelund, H.; Buhl, E. S.; Haase, C. L.; Johnsen, S. P.
Abstract: Aims: To identify individual predictors of early glycaemic control in people with Type 2 diabetes mellitus after initiation of first glucose‐lowering drug treatment in everyday clinical practice. Methods: Using medical registries, we identified a population‐based cohort of people with a first‐time glucose‐lowering drug prescription in Northern Denmark in the period 2000–2012. We used Poisson regression analysis to examine patient‐level predictors of success in reaching early glycaemic control [HbA1c target of < 53 mmol/mol (7%)] < 6 months after treatment start. Results: Among the 38 418 people (median age 63 years), 27 545 (72%) achieved early glycaemic control. The strongest predictor of achieving early control was pre‐treatment HbA1c level; compared with a pre‐treatment HbA1c level of ≤ 58 mmol/mol (7.5%), the adjusted relative risks of attaining early control were 0.63 (95% CI 0.61–0.64) for baseline HbA1c levels of > 58 and ≤ 75 mmol/mol (> 7.5 and ≤ 9%), and 0.58 (95% CI 0.57–0.59) for a baseline HbA1c level of > 9% (> 75 mmol/mol). All other examined predictors were only weakly associated with the chance of achieving early control. After adjustment, the only characteristics that remained independently associated with early control (in addition to high baseline HbA1c ) were being widowed (adjusted relative risk 0.95; 95% CI 0.93–0.97) and having a high Charlson comorbidity index score (score ≥ 3; adjusted relative risk 0.94; 95% CI 0.90–0.97). Conclusions: In a real‐world clinical setting, people with Type 2 diabetes mellitus initiating glucose‐lowering medication had a similar likelihood of achieving glycaemic control, regardless of sex, age, comorbidities and other individual factors; the only strong and potentially modifiable predictor was HbA1c before therapy start. What's new?: We examined predictors for attaining early glycaemic targets in drug‐naïve people with Type 2 diabetes mellitus in a large population‐based study. In a real‐world clinical setting, people who initiated glucose‐lowering medication had a similar likelihood of achieving glycaemic control regardless of sex, age group, comorbidities and other patient‐related factors. The only strong and potentially modifiable predictor was HbA1c before therapy start.